International Financial Management - Cheol S Eun and Bruce Resnick (Chennai, McGraw Hill Education, 2021)
The eighth edition of the text, just like the last seven editions, focus on the basics and managerial perspective. International Financial Management provides students with a foundation for analysis that will serve them well in their careers ahead. The decision-making process is presented through the text with the goal of teaching students how to make informed managerial decisions in an evolving global financial landscape. Already established as a popular textbook on the subject area, International Financial Management, 8e continues to take the legacy forward with recent updates. This edition will include: 1. New! Updated topic coverage on analysis of home bias and the cost of capital around the world, comparison of capital structure across countries, tax inversion maneuvers, swap trading practices under new financial regulation, and statistical presentation of market capitalizations and liquidity measurement in developed and developing countries 2. Management focus and theoretical rigor The framework for this text remains the same, which means it fits well in elective and advanced undergraduate and graduate courses 3. Thorough coverage Thorough coverage of financial markets and financial management is present, with the market$1 (Bs coverage presented early in the text 4. Case Applications These applications, incorporated into selected chapters, enhance topics and help students apply theories and concepts to real world situations 5. Wide array of pedagogical features such as (3z(BInternational Finance in Practice(3y (Bboxes, Certified Financial Analyst questions, Mini cases, (3z(BIn More Depth(3y (Bsections etc.s
Keywords: MBA; International Financial Management